Noninvasive Retinal Markers in Diabetic Retinopathy: Advancing from Bench towards Bedside - Søren Leer Blindbæk; Thomas Lee Torp; Kristian Lundberg; Kerstin Soelberg; Anna Stage Vergmann; Christina Døfler Poulsen; Ulrik Frydkjaer-Olsen; Rebecca Broe; Malin Lundberg Rasmussen; Jimmi Wied; Majbrit Lind; Anders Højslet Vestergaard; et al. (Journal of Diabetes Research)
The retinal vascular system is the only part of the human body available for direct, in vivo inspection. Noninvasive retinal markers are important to identity patients in risk of sight-threatening diabetic retinopathy. Studies have correlated structural features like retinal vascular caliber and fractals with micro- and macrovascular dysfunction in diabetes. Likewise, the retinal metabolism can be evaluated by retinal oximetry, and higher retinal venular oxygen saturation has been demonstrated in patients with diabetic retinopathy. So far, most studies have been cross-sectional, but these can only disclose associations and are not able to separate cause from effect or to establish the predictive value of retinal vascular dysfunction with respect to long-term complications. Likewise, retinal markers have not been investigated as markers of treatment outcome in patients with proliferative diabetic retinopathy and diabetic macular edema. The Department of Ophthalmology at Odense University Hospital, Denmark, has a strong tradition of studying the retinal microvasculature in diabetic retinopathy. In the present paper, we demonstrate the importance of the retinal vasculature not only as predictors of long-term microvasculopathy but also as markers of treatment outcome in sight-threatening diabetic retinopathy in well-established population-based cohorts of patients with diabetes.